Association of Previous Smoking Habit and Perceived Social Discrimination with the Risk of Multi-Drug Resistant Tuberculosis in Central Nepal - Marahatta, S B; Adhikari, B; Mishra, S R; Raut, S; Ramasoota, P; Malla, P; Kaewkungwal, J; Singhasivanon, P (Journal of Nepal Health Research Council, 2015)
Background: Multidrug-resistant tuberculosis (MDR TB) caused by Mycobacterium tuberculosis resistant to both Isoniazid and Rifampicin with or without resistant to other drug, is among the most alarming pandemic problem. The objectives of this study was to assess the risk factors of MDR TB in Central Nepal. Methods: A matched case control study was conducted among 186 cases of MDR TB and 372 non-MDR TB controls from central region of Nepal. Pretested questionnaires containing socio-economic, cultural & behavioral; environmental, biological and health service factors were used. Variables significant in bivariate analysis were entered in multiple regression models for further analysis. Results: After adjusting for confounders, previous smoking habit (aOR= 4.5,(95%CI(1.24-16.2)) (p=0.04), and perceived social discrimination (aOR=5.83,95%CI (1.77-19.71)) (P=0.021) independently predicted greater MDR TB risk. Conclusions: Encouraging MDR TB cases for smoking cessation through awareness activities should be a priority. Stigma reduction programs should include the empowerment of patients and communities while promoting TB related research for further exploration into the risk factors of TB and associated stigma. Keywords: Tuberculosis; drug resistance; smoking; stigma; Nepal